Selenium Yeast Dietary Supplement Affects Rumen Bacterial Population Dynamics and Fermentation Parameters of Tibetan Sheep (Ovis aries) in Alpine Meadow - Cui, Xiongxiong; Wang, Zhaofeng; Tan, Yuhui; Chang, Shenghua; Zheng, Huiru; Wang, Haiying; Yan, Tianhai; Guru, Tsedan; Hou, Fujiang (Frontiers in Microbiology, 2021)
Selenium deficiency is a widespread and seasonally chronic phenomenon amongst traditionally grazed Tibetan sheep on the Qinghai-Tibet Plateau. The effects of dietary addition of selenium-enriched yeast (SeY) on the sheep rumen bacterial community, and on rumen fermentation, were evaluated with the aim of gaining a better understanding of the rumen prokaryotic community. 24 yearling Tibetan rams (mean body weight c. 31kg), were divided randomly into 4 treatment groups, each of 6 rams, and fed a basic diet of fresh forage cut from alpine meadow, to which SeY was added at prescribed dose rates: control (CK), low Se (L), medium Se (M), high Se (H). This feed trial was conducted over 35 days during the warm season. On the final day, rumen fluid was collected using a transoesophageal sampler, for analysis of rumen pH, NH3-N, volatile fatty acids (VFA), and the rumen microbial community. These analyses showed that VFA and propionate concentrations for M group were significantly higher than those of CK and L groups (P < 0.05). The acetate concentration and acetate to propionate ratio for H group were significantly higher than for other groups (P < 0.05). Principal coordinate analysis (PCoA) and analysis of similarities (ANOSIM) both revealed that rumen bacterial population structure of each group was dissimilar. These differences were significant between the control group, and sheep treated with medium and high Se dose rates, but not significant between the control and group treated with low Se. The predominant rumen bacterial phyla were found to be Bacteroidetes, Firmicutes, and Proteobacteria; and the dominant three genera in all samples across all treatments: Christensenellaceae R7 group, Rikenellaceae RC9 gut group, and Prevotella 1. The relative abundance of Prevotella 1, Rikenellaceae RC9 gut group, Ruminococcus 2, Lachnospiraceae XPB1014 group, Carnobacterium, and Hafnia-Obesumbacterium were found to be significantly different between the four treatment groups (P < 0.05). Gene functions and metabolic pathways associated with the rumen metagenome were predicted using 16S rRNA-gene sequencing data. Results showed that Se dietary supplement did alter rumen environment parameters. To sum up, selenium significantly affected the abundance of rumen bacteria, and ultimately affected fermentation parameters.